Export Diversification Effects of the WTO Trade Facilitation Agreement - Cosimo Beverelli; Simon Neumüller; Robert Teh (FIW - Research Centre International Economics, 2015)
We estimate the effects of trade facilitation on export diversification, as measured by two extensive margins: the number of products exported by destination and the number of export destinations served by product. To address the issue of causality, we employ an identification strategy whereby only exports of new products, or exports to new destinations, are taken inton account when computing the respective margins of trade. We find a positive impact of trade facilitation on the extensive margins of trade. The results are robust to alternative definitions of extensive margins, different sets of controls and various estimation methods. Simulation results suggest substantial extensive margin gains from trade facilitation reform in Sub-Saharan Africa and Latin America and the Caribbean.
Keywords: F13; F14; F17; 330; Trade facilitation; Export diversification; International trade agreements; WTO